2023
DOI: 10.3390/foods12040801
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Role and Mechanisms of Essential Oils and Plant Extracts as Natural Preservatives to Extend the Postharvest Shelf Life of Edible Mushrooms

Abstract: China has a large variety of edible mushrooms and ranks first in the world in terms of production and variety. Nevertheless, due to their high moisture content and rapid respiration rate, they experience constant quality deterioration, browning of color, loss of moisture, changes in texture, increases in microbial populations, and loss of nutrition and flavor during postharvest storage. Therefore, this paper reviews the effects of essential oils and plant extracts on the preservation of edible mushrooms and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 165 publications
0
17
0
1
Order By: Relevance
“…SGP-1-1 (200 mg·kg –1 ·d –1 ) was observed to inhibit the TLR4-NF-κB pathway and modulate inflammation, enhancing SOD production and reducing cytokine and MDA levels. The hypoglycemic activity of SGP was evaluated through various models, supporting in vivo bioavailability investigations. ,,, Pregnancy is associated with a risk of insulin resistance and hyperinsulinemia . About 10% of pregnant women may develop gestational diabetes mellitus (GDM), with 3–5% experiencing postpregnancy diabetes .…”
Section: Health Benefits and Mechanism Of Actionmentioning
confidence: 92%
“…SGP-1-1 (200 mg·kg –1 ·d –1 ) was observed to inhibit the TLR4-NF-κB pathway and modulate inflammation, enhancing SOD production and reducing cytokine and MDA levels. The hypoglycemic activity of SGP was evaluated through various models, supporting in vivo bioavailability investigations. ,,, Pregnancy is associated with a risk of insulin resistance and hyperinsulinemia . About 10% of pregnant women may develop gestational diabetes mellitus (GDM), with 3–5% experiencing postpregnancy diabetes .…”
Section: Health Benefits and Mechanism Of Actionmentioning
confidence: 92%
“…By the end of the storage period, the mushrooms irradiated with 3 kGy were the softest, suggesting that higher doses of irradiation may accelerate the softening of KOM over time. Previous studies have reported that the firmness of shiitake mushrooms rapidly decreases during storage due to a combination of factors, including respiration, enzymatic activity and microbial contamination (Zhang et al, 2018;Guo et al, 2023). In addition, high doses of ionising radiation are known to reduce vegetable and fruit firmness (Guerreiro et al, 2016).…”
Section: Evaluation Of Ebi Impact On Kom Quality Attributes During St...mentioning
confidence: 99%
“…Pseudomonas spp., a member of the Gammaproteobacteria family, is evidenced to effectuate spoilage and contribute to the development of browning lesions in KOM (Azu Okorley et al, 2019). Moreover, KOM lacks a cuticle layer, unlike vegetables or fruits, which heightens their susceptibility to microbial infections (Guo et al, 2023), consequently complicating their storage and transportation. Additionally, post-harvest KOMs maintain their own physiological metabolism, including activation of respiration, which triggers cell wall disruption and aggravates texture (Akram & Kwon, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The quality deterioration of F. velutiper after harvesting severely limits its commercial value and hinders the development of the mushroom industry. Quality deterioration of mushrooms is characterized by a decline in the sensory and nutritional quality – i.e., a combination of the self and outer elements 27 . At present, research on the quality deterioration of mushrooms is mainly focused on the loss of water, weight, nutrition and flavor, microbial infestation, and changes in color, postharvest morphological characteristics and textural characteristics (Fig.…”
Section: Degradation Of the Quality Of F Velutipermentioning
confidence: 99%
“…1-MCP treatment 1-MCP is a highly effective ethylene inhibitor that competes irreversibly with ethylene for receptor binding sites and inhibits the role of ethylene in promoting ripening and senescence in fruits and vegetables. 27,[92][93][94] As a respiratory leap type of edible mushroom, the postharvest physiological metabolism of the golden mushroom is vigorous, and the rate of quality deterioration is closely related to the amount of ethylene released (Fig. 2 and Table 2).…”
Section: Antibacterial Cleaningmentioning
confidence: 99%